A new technique for selective identification and mapping of enhancers within long genomic sequences - Igor P. Chernov; Elena A. Stukacheva; Sergey B. Akopov; Dmitry A. Didych; Lev G. Nikolaev; Eugene D. Sverdlov (BioTechniques)
We report a new experimental method of direct selection, identification, and mapping of potential enhancer sequences within extended stretches of genomic DNA. The method allows simultaneous cloning of a quantity of sequences instead of tedious screening of the separate ones, thus providing a robust and high-throughput approach to the mapping of enhancers. The selection procedure is based on the ability of such sequences to activate a minimal promoter that drives expression of a selective gene. To this end a mixture of short DNA fragments derived from the segment of interest was cloned in a retroviral vector containing the neomycin phosphotransferase II gene under control of a cytomegalovirus (CMV) minimal promoter. The pool of retroviruses obtained was used to infect HeLa cells and then to select neomycin-resistant colonies containing constructs with enhancer-like sequences. The pool of the genomic fragments was rescued by PCR and cloned, forming a library of the potential enhancers. Fifteen enhancer-like fragments were selected from 1-Mb human genome locus, and enhancer activity of 13 of them was verified in a transient transfection reporter gene assay. The sequences selected were found to be predominantly located near 5′ regions of genes or within gene introns.